2022
DOI: 10.3390/en15145311
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Analysis of MV Electric Distribution Networks Including Distributed Generation and ICT Infrastructure

Abstract: In recent years, the increased distributed generation (DG) capacity in electric distribution systems has been observed. Therefore, it is necessary to research existing structures of distribution networks as well as to develop new (future) system structures. There are many works on the reliability of distribution systems with installed DG sources. This paper deals with a reliability analysis for both present and future medium voltage (MV) electric distribution system structures. The impact of DG technology used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Distribution system with PV unit at B/B5 The values of system performance indices like SAIFI, SAIDI, ENS and ASAI, for four different scenarios are obtained in Table 6 using Eq. ( 4) to (7). From the results in Table 6, it is observed that SAIDI and ENS are decreased from scenario 1 to scenario 4.…”
Section: B Case 2: the Distribution Systems Reliability Evaluation Wi...mentioning
confidence: 85%
See 2 more Smart Citations
“…Distribution system with PV unit at B/B5 The values of system performance indices like SAIFI, SAIDI, ENS and ASAI, for four different scenarios are obtained in Table 6 using Eq. ( 4) to (7). From the results in Table 6, it is observed that SAIDI and ENS are decreased from scenario 1 to scenario 4.…”
Section: B Case 2: the Distribution Systems Reliability Evaluation Wi...mentioning
confidence: 85%
“…For the capacity of 1.5 MW,1.85 MW,2.97 MW of PV and for different location of PV, system reliability indices are calculated using Eq. from (4) to (7) and radial distribution network is reliable when PV located at busbar 5. This comparison highlights how the placement of PV systems affects the SAIDI and ENS under these specific conditions.…”
Section: ) Distribution System With Pv Unit With the Capacity Of 15 M...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, systemic reliability indices [29] are calculated for the power system under investigation reported in Table 5. According to SAIFI and SAIDI values, each customer of the considered urban hybrid grid averagely experiences 11 min of outages in a year.…”
mentioning
confidence: 99%